Limnological notes on Nilsagar, Nilphamari, Bangladesh - Islam, Md Shafiqul; Gani, Md Ataul; Alfasane, Md Almujaddade; Khondker, Moniruzzaman (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(1): 75-78, 2013 (January)